If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -6) + -1(-9x + -1) = 11x + -5 Reorder the terms: (-6 + 2x) + -1(-9x + -1) = 11x + -5 Remove parenthesis around (-6 + 2x) -6 + 2x + -1(-9x + -1) = 11x + -5 Reorder the terms: -6 + 2x + -1(-1 + -9x) = 11x + -5 -6 + 2x + (-1 * -1 + -9x * -1) = 11x + -5 -6 + 2x + (1 + 9x) = 11x + -5 Reorder the terms: -6 + 1 + 2x + 9x = 11x + -5 Combine like terms: -6 + 1 = -5 -5 + 2x + 9x = 11x + -5 Combine like terms: 2x + 9x = 11x -5 + 11x = 11x + -5 Reorder the terms: -5 + 11x = -5 + 11x Add '5' to each side of the equation. -5 + 5 + 11x = -5 + 5 + 11x Combine like terms: -5 + 5 = 0 0 + 11x = -5 + 5 + 11x 11x = -5 + 5 + 11x Combine like terms: -5 + 5 = 0 11x = 0 + 11x 11x = 11x Add '-11x' to each side of the equation. 11x + -11x = 11x + -11x Combine like terms: 11x + -11x = 0 0 = 11x + -11x Combine like terms: 11x + -11x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 19=4(k+1)-k | | (7x-4)=-27 | | 39.9-59.2= | | c-3=4.7 | | c-3=4.5 | | -13-9= | | -(-4u-x+6)= | | y-(-4)=4.3 | | 9k^2+66k+21=0 | | 4x-6=7x+6 | | 27=v+(-5) | | 16c-10b=2 | | 9t-21+3t+10=1 | | 7a^2+53a+28=0 | | .67(m-8)=4 | | 4(2b-6)+11+8b=-13 | | 2-3(x-1)=4-2(x-3) | | 2n^2+5n+2=0 | | .75(x+9)=15 | | 5x-8=0 | | 2v^2+11v+5=0 | | 5=4(n+2)-n | | 8t^3-32t+8=0 | | 5n^2+19n+12=0 | | 4(x+3)-x=0 | | -13=n+(-39) | | y^2+3y=5 | | 10=-6+x | | 21=6r+5-7c | | 15=3(c-1)+9 | | 3(f+2)+9-5f=13 | | 4(x+1)=2(x-1) |